2021
DOI: 10.1002/for.2769
|View full text |Cite
|
Sign up to set email alerts
|

The information content of uncertainty indices for natural gas futures volatility forecasting

Abstract: We investigate the information content of five uncertainty indices for the US natural gas futures volatility forecasting. Our investigation is based on the GARCH-MIDAS framework. The in-sample outcomes suggest that most of uncertainty indices have a crucial effect on natural gas futures volatility. And the out-of-sample prediction results indicate that the geopolitical risk (GPR) and equity market volatility (EMV) indices contain more useful information for natural gas futures volatility. Moreover, according t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 78 publications
(8 citation statements)
references
References 50 publications
0
8
0
Order By: Relevance
“…Abosedra et al ( 2006 ) developed a forecasting model for natural gas futures contracts and discovered that futures prices a month in advance were beneficial as a forecasting device. Liang et al ( 2021 ) used a GARCH-MIDAS framework-based forecasting model and found that geopolitical risk and equity market volatility provide useful information on natural gas futures volatility. In this case, very limited information is available regarding appropriate forecasting techniques for natural gas futures.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Abosedra et al ( 2006 ) developed a forecasting model for natural gas futures contracts and discovered that futures prices a month in advance were beneficial as a forecasting device. Liang et al ( 2021 ) used a GARCH-MIDAS framework-based forecasting model and found that geopolitical risk and equity market volatility provide useful information on natural gas futures volatility. In this case, very limited information is available regarding appropriate forecasting techniques for natural gas futures.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Fluctuations in the gold and stock markets are easily affected by global market conditions, their dynamic changes are relevant indicators of expectations about the future state of the global economy ( Baur and Lucey, 2010 ; Choudhry et al, 2015 ; Jaffe, 1989 ; Liang et al, 2020 , 2021 ). The econometric construction connecting the both markets originate from the long-run linkage between them, and their prices have wide impacts on worldwide macroeconomic fundamentals ( Cai et al, 2001 ).…”
Section: Gold and Stock Markets And Covid-19mentioning
confidence: 99%
“…In addition, motivated by Baker et al (2016) , Baumeister et al (2022) , Caldara and Iacoviello (2022) , and Baumeister and Hamilton (2019) , we mainly employ four indicators to capture changes in various aspects of global conditions, namely, the global economic policy uncertainty index, global economic conditions index, geopolitical risk index, and world industrial production index. A great number of works have put forward strong evidence of the significant relationship between energy markets and exogenous indicators, including uncertainty indices ( Hong et al, 2022b ; Li, Liang, et al, 2022 ; Liang et al 2020 , 2021 ), climate-related indicators ( Considine, 2000 ; Hong et al, 2022c ; Liang, Umar, et al, 2022 ) and macroeconomic fundamentals ( Doroodian & Boyd, 2003 ; Taghizadeh-Hesary et al, 2016 ; Lacheheb & Sirag, 2019 ). One of these branches of research has focused on crude oil and natural gas markets, while little attention has been given to gasoline and heating oil markets ( Olanipekun et al, 2019 ; Olubusoye et al, 2021 ; Al-Thaqeb et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…A great number of studies on forecasting the price volatility of energy markets take crude oil markets as their main research object ( Balcilar et al, 2021 ; Fan et al, 2007 ; Hong et al, 2022a ; Huang et al, 2022 ). Furthermore, as one of the most important energy resources in the US, natural gas has also received much attention from scholars ( Dai & Zhu, 2022 ; Liang et al, 2021 ; Wang, Ma, et al, 2022 ). Relatively little attention has been given to gasoline and heating oil ( Baumeister et al, 2018 ; Olanipekun et al, 2019 ; Mensi et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%